OAI-ORE, PRESERV2 and Digital Preservation - Rumsey, S; O'Steen, B (UKOLN, 2008)
The new framework for the description and exchange of aggregations of Web resources, OAI-ORE, had its European release in April 2008 [1]. Amongst its practical uses, OAI-ORE has a role to play in digital preservation and continued access to files. This article describes the basic outline of the framework and how it can support the PRESERV2 project digital preservation model of provision of preservation services and interoperability for digital repositories. The PRESERV approach recognises that effective preservation is founded on three fundamental actions on data: copy, move and monitor. This includes the copying and movement of data between different repositories which is where OAI-ORE has a role to play. OAI-ORE also plays a part in interoperability to ensure that repositories and other tools and services can communicate and share information and data. In this way the project is creating and testing a flexible framework for an emerging range of services and tools, to ensure support for long-term access to the data deposited in repositories.